2005
DOI: 10.1111/j.1600-0447.2005.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered neural circuit for working memory before and after symptom provocation in patients with obsessive–compulsive disorder

Abstract: The interaction between symptom provocation and WM occurring in the fronto-striatal system may hold the key to the neurobiology of OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
6
21
2
Order By: Relevance
“…For example, significantly higher metabolic activity has been observed in the fronto-subcortical circuitry in patients with OCD, and this elevated activation is hypothesized to arise from disinhibition that, in turn, may be related to psychopathological symptoms such as inability to control reflexive responses and to regulate social behavior [Baxter et al, 1987[Baxter et al, , 1988Benkelfat et al, 1990;Insel, 1992;Kang et al, 2004;Machlin et al, 1991;McGuire et al, 1994;Shin et al, 2006;Swedo et al, 1989]. As for the neural bases of perceptual impairments in OCD, there is no direct evidence implicating deficits in the sensory visual pathways.…”
Section: Introductionmentioning
confidence: 99%
“…For example, significantly higher metabolic activity has been observed in the fronto-subcortical circuitry in patients with OCD, and this elevated activation is hypothesized to arise from disinhibition that, in turn, may be related to psychopathological symptoms such as inability to control reflexive responses and to regulate social behavior [Baxter et al, 1987[Baxter et al, , 1988Benkelfat et al, 1990;Insel, 1992;Kang et al, 2004;Machlin et al, 1991;McGuire et al, 1994;Shin et al, 2006;Swedo et al, 1989]. As for the neural bases of perceptual impairments in OCD, there is no direct evidence implicating deficits in the sensory visual pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Brain imaging techniques, including computerized tomography (CT) and magnetic resonance imaging (MRI), have revealed morphological changes in the basal ganglia or frontal lobe of OCD patients (Grachev et al, 1998;Hoehn-Saric & Green-berg, 1997;Kim et al, 2001;Szeszko et al, 1999). Positron emission tomography (PET) and functional magnetic resonance imaging (f MRI) studies have also revealed abnormal activation in the striatum, orbitofrontal cortex, thalamus, and cingulate gyrus during the resting state (Baxter et al, 1992;Perani et al, 1995), as well as symptom provocation (Rauch et al, 1996;Shin et al, 2006) and cognitive activation (Pujol et al, 1999;Rauch et al, 1997). Unlike brain imaging studies, neuropsychological studies have shown impairments in various cognitive domains in OCD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of activation in the rDLPFC in OCD patients during visual working memory tasks is telling, given the general importance of this area in tasks of executive functioning and visual working memory. Shin et al ( 2006 ) also found increased activation in the anterior cingulate (AC) during working memory tasks in OCD patients after symptom provocation. Because the AC is important for anxiety control, Shin et al ( 2006 ) posited that the AC might operate to control anxiety in OCD patients during working memory tasks by focusing attention on solving a problem at hand.…”
Section: Neuroimaging Of Working Memory In Ocdmentioning
confidence: 93%
“…Using a PET scan, Shin et al ( 2006 ) compared the neurophysiology of visual working memory in OCD patients ( n = 12) to nonclinical controls ( n = 12) matched for age and sex. The OCD group committed more errors than did the healthy control group on the working memory task.…”
Section: Neuroimaging Of Working Memory In Ocdmentioning
confidence: 99%
See 1 more Smart Citation